Educational Management Strategies in Implementing Central Approaches for Early Childhood Learning in Kindergarten - Irenne Kusminarso; Indah Arvianti; Didit Kurniadi (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze educational management strategies in implementing a child-centered approach to early childhood learning in kindergarten settings. Using a descriptive qualitative approach with a case study design, the research was conducted at TK Cahaya Bangsa in Semarang, Central Java. Data were collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that the educational management strategies include thematic curriculum planning, flexible scheduling, participative leadership, and active parental involvement. The child-centered approach is implemented through project-based learning, environmental exploration, and thematic activities that position children as active participants in the learning process. The main challenges identified involve limited learning resources, varying teacher competencies, and fluctuating levels of parental engagement. Nevertheless, effective management strategies significantly contribute to creating a child-centered learning environment that fosters autonomy, creativity, and social development. This study offers valuable implications for early childhood education policy and managerial practices in preschool institutions. Keywords: educational management, child-centered approach, early childhood education, kindergarten, child-centered learning